2014
DOI: 10.1002/bate.201300077
|View full text |Cite
|
Sign up to set email alerts
|

Mit Schrauben fügen und bewehren – Langzeitversuche an biegesteifen Rahmenecken im Außenklima

Abstract: Seit 2006 werden am Lehrstuhl für Tragkonstruktionen der RWTH Aachen (Trako) Fügungen und Verstärkungen von Holzbauelementen mit als Bewehrung angeordneten selbstbohrenden Vollgewindeschrauben entwickelt. Sehr positive Ergebnisse wurden in Versuchen mit biegesteifen Rahmenecken für positive und negative Biegemomente erzielt, die im Kurzzeitversuch Bruchlasten von über 80 % der reinen Querschnittstragfähigkeit erreichten. Die hohe Tragfähigkeit bedingt dabei eine entsprechend hohe Auslastung sowohl des Holzquer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[17], [18]. There are first experiences available for reinforced beams under varying dynamic climate, [9], [6], [19], [20]. Sjödin [20] confirms an indeed reduced load-bearing capacity of steel-timber dowel joints loaded parallel to the grain under initial drying exposure.…”
Section: Reinforcements In Timber Struct-ures Under Climate Exposurementioning
confidence: 80%
See 2 more Smart Citations
“…[17], [18]. There are first experiences available for reinforced beams under varying dynamic climate, [9], [6], [19], [20]. Sjödin [20] confirms an indeed reduced load-bearing capacity of steel-timber dowel joints loaded parallel to the grain under initial drying exposure.…”
Section: Reinforcements In Timber Struct-ures Under Climate Exposurementioning
confidence: 80%
“…Likewise, the increasing influence of end-grain moisture transport was not considered. Trautz [6] measured the deformations of self-tapping screws as connectors and reinforcements on rigid frame corners in exterior climatic to evaluate the creep of the screws and the connections. The results for the specimens with a high degree of utilization also show a decrease of load-bearing capacity after an exterior exposure of 2 years.…”
Section: Reinforcements In Timber Struct-ures Under Climate Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The significant impact of crack formation on shear resistance and the desire to prevent the spread of already existing cracks encourages the strengthening of beams. From numerical and experimental studies on shear reinforcement by means of GiR or self-tapping screws [13][14][15][16][17][18] it can be concluded that GiR (and self-tapping screws) set under an angle of 45° with respect to the beam axis provide an efficient mean of increasing the shear strength of beams. Beams strengthened in shear will reach higher load bearing capacities in bending since early shear failures are prevented.…”
Section: Strengthening In Shearmentioning
confidence: 99%